Optical studies of rocket exhaust trails and artificial noctilucent clouds produced by Soyuz rocket launches. Issue 14 (16th July 2013) - Dalin, P.; Perminov, V.; Pertsev, N.; Dubietis, A.; Zadorozhny, A.; Smirnov, A.; Mezentsev, A.; Frandsen, S.; Grønne, J.; Hansen, O.; Andersen, H.; McEachran, I.; et al.
Abstract: [1] Detailed tracing of an exhaust plume from a rocket's initial trajectory is a scientifically and diagnostically useful technique. It can provide detailed information on the atmosphere's mean winds, wind shears, turbulent regime, and physical state over a wide altitude range from 50 to 200 km. We analyze Soyuz rocket exhaust plumes from Plesetsk on 21 May 2009 and 27 June 2011, which uncovered significantly different atmospheric states and underlying dynamics. The first case showed highly dynamical conditions in the mesosphere, characterized by vortex structures, wind shears, and small‐scale turbulent eddies. The estimated turbulent energy dissipation rates ranged 330–460 mW kg −1 . A characteristic balloon‐shaped trail was observed at altitudes between 105 and 160 km, having rapid expansion rates of 500–800 m s −1 over the time period of 2 min which can be explained by complex gas dynamic processes in the rocket wake involving the collision of shock waves. In the second case, we show evidence that the rocket exhaust trail persisted without any changes during its motion from Plesetsk via Denmark to the UK for 9 h, indicating extremely stable atmospheric conditions. This case introduces a new state of the summer mesosphere—remarkably quiet conditions, probably never observed before. The rocket plumes studied, related to the initial rocket trajectory, are essentially twilight phenomena as seen from the ground using wideband spectrum cameras, that is, the Sun should be below the horizon by 6°. For the first time, we analyze the dynamics of rocket exhaust products at the initial trajectory in the mesosphere and lower thermosphere using detailed photographic imaging taken from the ground. Key Points: Soyuz rocket launches uncovered different atmospheric states and dynamics A characteristic balloon‐shaped trail was observed between 105 and 160 km A rocket exhaust trail persisted without any changes during its motion for 9 hrs